Microbiological Air Quality in Food Services of Childcare Institutions in Barranquilla, Colombia - Morales-Pinto, Nuris
The research aimed to assess the microbiological quality of air in food services of childcare institutions in Barranquilla, Colombia. A randomized block experiment was conducted involving 30 childcare institutions as blocks or repetitions and three (3) treatments representing storage, processing, and dining areas. Sampling was performed in each establishment after cleaning and disinfection, and before food preparation. Two hygiene indicators for air microbiological quality were analyzed: mesophilic aerobes and mold and yeast, using the sedimentation method on Petri dishes with Plate Count Agar and Yeast Extract Glucose Chloramphenicol Agar (YGC Agar), respectively. Results revealed mesophilic aerobes, molds, and yeasts in storage, processing, and dining areas in some food services. These findings indicate insufficient cleaning and disinfection procedures, promoting the growth of microorganisms. Implementation of a basic sanitation plan, promotion of health education training for handling staff, and adherence to basic principles of good manufacturing practices are necessary to protect the health and well-being of the child population in these institutions.